1ISG-026 Forthcoming indication of oral anticoagulants for coronary artery and peripheral arterial disease: prevalence of diseases and pharmaceutical expenditure estimation. (March 2019) - Degli Esposti, L; Girardi, A; Veronesi, C; Perrone, V; Degli Esposti, E; Castello, R; Roncon, L; Scroccaro, G; Mantoan, D; Andretta, M
Abstract : Background: The European Medicines Agency has recently approved rivaroxaban for the prevention of atherothrombotic events in patients with coronary artery disease (CAD) and peripheral arterial disease (PAD). Purpose: The present study aimed at analysing the prevalence of CAD and PAD among the health-assisted population and to estimate the pharmaceutical expenditure. Material and methods: Data have been obtained by retrospectively analysing a regional healthcare database between 1 January 2017 and 31 December 2017. We included adult patients (≥18 years) with a diagnosis of CAD (at least one prescription of nitrates and/or CAD diagnosis at hospital discharge) and a diagnosis of PAD (at least one prescription of antiplatelet drugs with concomitant prescription of anti-hypertensive agents or lipid-lowering agents and/or PAD diagnosis at hospital discharge). Patients were characterised over the period 2009–2016 for comorbidities (diabetes mellitus, heart failure, chronic kidney disease, cardiovascular event), during 2016 for drug use. Treatment adherence was calculated using the Medication Possession Ratio. Results: More than 4.9 million health-assisted participants, 8.8% (430, 254, mean age 74.2 years) received a diagnosis of CAD or PAD (41.2% PAD, 30.4% CAD, 28.4% both). Forty-two per cent (180, 551) of patients had at least one comorbidity. Most frequently prescribed cardiovascular agents were anti-hypertensives (85%), antiplatelet drugs (58.7%), lipid-lowering drugs (53%) and anticoagulants (17.2%). Among patients treated with antiplatelet drugs, 36.2% were adherent to treatment. Considering the actual price of rivaroxaban, the pharmaceutical expenditure for one-year treatment in the considered region resulted at €266 million (€38 million is the current pharmaceutical expenditure for new anticoagulant therapies for 2018). Applying this analysis for patient sub-groups, the estimation was €191 million for patients with CAD or PAD, €75 million for patients with both and €112 million for those with at least one comorbidity. Considering patients adherent to antiplatelet treatment, the estimation was €58 million. Conclusion: Nearly one out of ten health-assisted subjects had CAD and PAD diagnosis, in accordance with that already published for the national population. Pharmaceutical costs' estimations represent the maximal costs as they did not consider the possible reduction in drug prices negotiated by the National Medicines Agency, considering the significant market increase and redeemability limitations. References and/or acknowledgements: No conflict of interest.